HUBUNGAN JENIS KELAMIN DENGAN KALSIFIKASI AORTA PADA RADIOGRAFI TORAKS - Elizabeth Katherine Tanzil; Inge Friska Widjaya (Universitas Pahlawan, 2022)
Atherosclerosis is an asymptomatic condition and one of the leading causes of heart attacks and strokes, which is the leading cause of death worldwide. Atherosclerosis that appears as a calcification in the aortic arch can be detected by chest radiograph. The exact cause of atherosclerosis is unknown, but the Framingham Heart Study states that gender is one of the risk factor that increases the incidence of cardiovascular disease. This research aims to determine the relationship between gender and aortic calcification on chest radiograph. This research was conducted by using the analytical observasional method with a cross-sectional approach. The data taken was the data contained in the chest radiograph of patients who have had a chest radiograph at the Rumah Sakit Royal Taruma Jakarta Barat in January 2022 using a consecutive sampling that adjusted to the inclusion and exclusion criteria. The collected samples were subsequently analysed by using Pearson Chi-square test with Statistical Product and Service Version 26. From total 160 samples, grade 0 aortic arch calcification was showed in 9 men (11.3%) and 21 women (26.3%), grade 1 in 30 men (37.5%) and 33 women (41.3%), grade 2 in 31 men (38.8%) and 21 women (26.3%), grade 3 in 10 men (12.5%) and 5 women (6.3%). The conclusion of this study was that there was a significant relationship between gender and aortic calcification on chest radiograph at the Rumah Sakit Royal Taruma Jakarta Barat with p-value = 0.036 (p-value < 0.05).